Scoping Review: Pola Penggunaan Antipsikotika Pada Pasien Skizofrenia Paranoid - Cotama, Cahana Rastra; Yulistiani (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2025)
Paranoid schizophrenia has a better prognosis than other forms. The main sign of paranoid schizophrenia is having strong delusions or auditory hallucinations. This review article is prepared to study the patterns of antipsychotic treatment in schizophrenia patients. The literature sources include PubMed and Google Scholar over the past decade. The PICO screening procedure yielded 6 publications utilized as primary data. This review's findings suggest that the principal objective of antipsychotic treatment in people with schizophrenia is to attain remission swiftly and safely. Atypical antipsychotics are the primary treatment option for schizophrenia, specifically Risperidone, Aripiprazole, Olanzapine, Quetiapine, and Clozapine. The implementation of combination therapy is contingent upon the severity of schizophrenia symptoms. Using combinations of antipsychotics will lead to a wider range of receptor targets, which will make antipsychotics work better. In combination therapy, typical antipsychotics are utilized due to their swift alleviation of positive symptoms, including hallucinations and delusions. Paranoid schizophrenia for achieving early remission is capable of utilizing atypical monotherapy, combination of typical and atypical, combination of atypical and atypical antipsychotics in reaching remission with symptom assessments using PANSS and GAF.